PERGESERAN HUKUM PROSES BERPERKARA DI INDONESIA DITINJAU DARI PERSPEKTIF SIYASAH DUSTURIYAH - Mustaqim Mustaqim; Farida Arianti; Hebby Rahmatul Utamy (UIN Mahmud Yunus Batusangkar, 2023)
TheprobleminthisresearchishowthelegalsystemoflitigationinIndonesiaandthelegalsystem of litigation in Indonesia from the siyasah dustiriyah perspective. The purpose of thisresearchistofindouthowthelegalsystemforlitigationinIndonesiaandthelegalsystemforlitigationfromthesiyasadusturiahperspective.Thetypeofresearchusedisthetypeoflibrary research or (library research) which is normative juridical. The data source in thisresearch is a secondary data source. Secondary data sources consist of: primary legalmaterials, secondary legal materials. Primary legal material for this research comes from acollection of legal materials in the form of legislation related to research, and secondary legalmaterialsintheformofmaterialsthatprovideexplanationsorsupportandexplorestatutoryregulationsfrombooks,articlesandjournals.Theresultsofthestudyshowthattheshiftinthe litigation process from HIR and RBg to Perma No. 1 of 2019 is seen in 3 stages, namely:thepreparationstage,theexaminationstageandthedeterminationstage.TheshiftinPermaNo.1of2019onlyappliestolitigantsanddoesnotapplytotheinternalcourtenvironment,because the purpose of enacting this Perma is to make it easier for the community to resolvetheir cases and to support the principles of a simple, fast and low-cost trial. According toSiyasa'sperspective.